Комбіновані сорбенти на основі бавовняного волокна та фероціанідів перехідних металів - Galysh, V. V.; Каrtel, M. T.; Nikolaychuk, A. A.; Andrusishina, I. N. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2012)
Combined sorbents based on cotton fiber and ferrocyanide of transition metals were obtained. The influence of the concentration of ferrocyanide and temperature of modification process on the inorganic component content in the final product were studied. The parameters of the modification process which allows to obtain samples of sorbents with stable content of ferrocyanide phase. Efficiency of removal of cesium from the model solutions by the obtained combined materials decreases in the order: Cu2+ - Fe3+ - Zn2+ - Ni2+ - Сo2+.